Force control-based vibration suppression in robotic grinding of large thin-wall shells. (February 2021) - Wang, Qilong; Wang, Wei; Zheng, Lianyu; Yun, Chao
Highlights: A robotic large thin-wall grinding workcell with a novel force controlled end-effector is proposed. The vibration suppression mechanism of force control-based robotic grinding is explained and validated. The contact force-vibration response function is developed, and the force control-based vibration control method of large thin-wall grinding is designed. With the novel method, vibration can be effectively suppressed and material removal is not affected. Abstract: Vibration suppression is a major difficulty in the grinding of low-stiffness large thin-wall shells. The paper proposes that effective workpiece vibration control can be performed by a novel force-controlled end-effector integrated into a robotic grinding workcell. First, a dynamics model is built to capture the characteristics and vibration suppression mechanism of force control-based robotic grinding, then a novel force control-based vibration suppression method is designed for grinding large thin-wall shells, and three robotic grinding tests are conducted to validate the effects of the new method and the grinding performance of the force control-based robotic grinding workcell. The results are: 75% reduction in the amplitude of workpiece vibration; effective suppression of non-tool passing frequency; stable grinding of large thin-wall shells remarkably enhancing grinding depth up to 0.3 mm per pass, grinding depth error less than ±0.1 mm, and significant improvement of the workpiece surface quality up to Ra=0.762 μm.